Development of 3D E-FIST as A Teaching Material for E-Learning on Temperature and Heat Materials - Tuti Patmawati; Abd. Kholiq (Universitas Lambung Mangkurat, 2021)
This study aims to describe the validity of E-FIST (Ebook Fisika STEM), namely the STEM physics ebook as e-learning teaching materials on temperature and heat material. The stages of development in this study were limited to the validity of the media, not up to practically and effectiveness trials in learning by students, this was due to the PSBB which was carried out in the prevention of the spread of Covid-19. The ebook was developed by integrating science, technology, engineering, and mathematics. This research was developed with the DDD-E model. The stages of the DDD-E model consist of the planning stage (decide), the design stage (design), the development stage (develop), and the assessment stage (evaluate). At the initial stage, namely planning, determining the learning objectives, material, knowledge analysis, and prerequisite skills was carried out so that a draft E-FIST was produced for further evaluation. The next stage is the development stage. After an assessment was carried out at the development stage, three expert lecturers were validated for E-FIST. The aspects that are validated are viewed from the aspects of learning, material, language, and media. The analytical method used is descriptive quantitative analysis. Based on the research results it can be concluded that E-FIST obtains a percentage of validity in terms of aspects of learning, material, language, media suitability with the principles of good learning media, media work processes, and media display respectively were categorized as very good, so that the E-FIST developed was declared very valid and suitable for use in learning. This research implies that it can provide further knowledge for educators regarding the use of ebook technology as the development of teaching materials. Also, further researchers, it can be carried out to test the effectiveness and practically to produce teaching materials that are suitable for use in supporting learning.